Evaluation of Accounting Policies for the Recognition, Measurement, and Presentation of Ex-Liquidation Assets: A Case Study of Institution XYZ (E-Jurnal Akuntansi, 2026)
Institution XYZ faces challenges in reformulating accounting policies for ex-liquidation assets following findings by the Supreme Audit Agency. This study aims to evaluate the asset recognition policy against the Conceptual Framework for Financial Reporting, ensure that the measurement policy achieves relevance and faithful representation, and verify that the presentation policy adheres to principles of transparency and public accountability. The research utilizes data collection methods comprising documentation, interviews, and benchmarking. The findings indicate that the policy of recognizing these items as contingent assets is inconsistent with the conceptual framework, as the items meet the definition of an asset. Regarding measurement, due to the absence of an active market for ex-liquidation assets, Institution XYZ employs a Level 3 fair value measurement hierarchy with the assistance of independent appraisers. The asset presentation policy classifies these assets within the Statement of Financial Position to enhance faithful representation; however, the disclosure of estimation uncertainty requires improvement to align with transparency principles. The transition to on-balance-sheet recording necessitates an initial assessment and more reliable measurement.
Keywords: ex-liquidation assets; conceptual framework for financial reporting; accounting policy; accounting information